Composite films and methods of making and using same

A composite film of nanostructured metal oxide crystals and proton-conducting polymers addresses the conductivity issues in PEMFCs by providing enhanced proton conductivity and stability, allowing operation up to 300°C.

JP7605744B2Active Publication Date: 2024-12-24BOARD OF RGT THE UNIV OF TEXAS SYST
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021548541
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-10-31
Filing Date
2019-10-30
Publication Date
2024-12-24
Estimated Expiration
2039-10-30

AI Technical Summary

Technical Problem

Existing proton exchange membranes for fuel cells face challenges in maintaining proton conductivity above 100°C due to dehydration and instability, limiting the operating temperature and efficiency of proton exchange membrane fuel cells (PEMFCs).

Method used

A composite film comprising nanostructured metal oxide crystals dispersed in a proton-conducting polymer phase, where the metal oxide crystals provide proton retention and the polymer phase offers a conductive pathway, enhancing proton conductivity across a wide temperature range.

Benefits of technology

The composite film achieves proton conductivity up to five orders of magnitude higher than individual components, enabling PEMFCs to operate efficiently at temperatures up to 300°C with improved stability and reduced susceptibility to coking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605744000001
    Figure 0007605744000001
  • Figure 0007605744000002
    Figure 0007605744000002
  • Figure 0007605744000003
    Figure 0007605744000003
Patent Text Reader

Abstract

Disclosed herein is a composite film comprising a plurality of nanostructured metal oxide crystals having an average particle size of 1 nm to 20 nm dispersed within a proton-conducting polymer phase, the composite film comprising 20 to 90 volume % of the plurality of nanostructured metal oxide crystals. This composite film exhibits a thermal conductivity of 100°C or higher at temperatures of 100°C or higher. -8 It can have a proton conductivity of 5 S / cm or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority to U.S. Provisional Patent Application No. 62 / 753,271, filed October 31, 2018, the entirety of which is incorporated herein by reference. [Background technology]

[0002] Proton exchange membranes are used in proton exchange membrane fuel cells (PEMFCs) or some electrochromic devices to transport protons between negative and positive electrodes during charging and discharging. There are current challenges to operate PEMFCs at higher temperatures, e.g., above 100°C, for increased electrochemical efficiency and stability. However, the number of materials that exhibit proton conduction above 100°C is limited, and existing ones exhibit either stability issues, scalability issues, or insufficient performance. Existing ideas usually use solid forms of acids with excess protons (which are unstable under humid conditions), organic-inorganic materials that are mixed with organic polymers and inorganic components (usually metal hydrates), where proton conduction occurs from water molecules held by the hydrates (which negate their beneficial effect when desorbed at high temperatures), and various organic coating layers that help prevent dehumidification of the membrane. Thus, there is a need for materials that exhibit stable and sufficient proton conduction above 100°C in addition to conductivity under ambient conditions. The compositions and methods discussed herein address such needs. Summary of the Invention [Problem to be solved by the invention]

[0003] In accordance with the objectives of the disclosed compositions and methods, as embodied and broadly described herein, the disclosure relates to composite films and methods of making and using same. [Means for solving the problem]

[0004] In some examples, disclosed herein is a composite film comprising a plurality of nanostructured metal oxide crystals having an average particle size of 1 nm to 20 nm dispersed within a proton conducting polymer phase, the composite film comprising 20% ​​to 90% by volume of the plurality of nanostructured metal oxide crystals.

[0005] In some examples, the plurality of nanostructured metal oxide crystals comprises a reducible metal oxide. In some examples, the plurality of nanostructured metal oxide crystals comprises niobium oxide, titanium oxide, tungsten oxide, zirconium oxide, hafnium oxide, magnesium oxide, vanadium oxide, iron oxide, chromium oxide, manganese oxide, nickel oxide, cerium oxide, gadolinium oxide, samarium oxide, or combinations thereof. In some examples, the plurality of nanostructured metal oxide crystals comprises niobium oxide, titanium oxide, tungsten oxide, hafnium oxide, vanadium oxide, iron oxide, chromium oxide, manganese oxide, nickel oxide, cerium oxide, gadolinium oxide, samarium oxide, or combinations thereof. In some examples, the plurality of nanostructured metal oxide crystals comprises cerium oxide. In some examples, the plurality of nanostructured metal oxide crystals comprises cerium oxide doped with one or more dopants. In some examples, the plurality of nanostructured metal oxide crystallites comprises gadolinium doped cerium oxide, samarium doped cerium oxide, or a combination thereof.

[0006] In some examples, each of the plurality of nanostructured metal oxide crystals has at least one dimension that is between 1 nm and 5 nm in size. In some examples, the plurality of nanostructured metal oxide crystals has an average grain shape that is substantially isotropic. In some examples, the plurality of nanostructured metal oxide crystals has an average grain size between 1 nm and 10 nm.

[0007] In some instances, the plurality of nanostructured metal oxide crystals are substantially free of ligands and / or capping materials.

[0008] In some examples, the proton conducting polymer phase comprises a polyether, a polysulfonate, a polysulfone, a poly(imidazole), a triazole, a benzimidazole, a polyester, a polycarbonate, a polymer derived from a pyridine monomer, a derivative thereof, or a combination thereof. In some examples, the proton conducting polymer phase comprises a polyether or a derivative thereof. In some examples, the proton conducting polymer phase comprises a polyethylene oxide, a polyetherpyridine, a polyetheretherketone (PEEK), a polytetrahydrofuran, a polyvinylbutyral, a polybenzimidazole, a derivative thereof, or a combination thereof. In some examples, the proton conducting polymer comprises a polyethylene oxide, a polytetrahydrofuran, a derivative thereof, or a combination thereof.

[0009] In some examples, the composite film comprises 30% to 90%, 20% to 70%, or 20% to 50% by volume of the composite film. In some examples, the composite film has an average thickness of 100 nm to 500 μm, 1 μm to 500 μm, or 10 μm to 100 μm. In some examples, the composite film is heated to 100° C. at a temperature of 25° C. or more, 100° C. or more, 200° C. or more, or 300° C. or more. -8 S / cm or more, 10 -6 S / cm or more, 10 -4 In some embodiments, the composite film has a proton conductivity of at least 0.01 S / cm, or at least 0.1 S / cm. In some embodiments, the composite film forms a free-standing membrane. In some embodiments, the composite film is supported by a substrate.

[0010] Also disclosed herein is a method of making any of the composite films described herein, comprising dispersing a plurality of nanostructured metal oxide crystals, and a polymer comprising a proton conducting polymer phase in a solvent, thereby forming a dispersion; and depositing the dispersion onto a substrate, thereby forming the composite film.

[0011] In some examples, the solvent comprises tetrahydrofuran (THF), dimethylformamide (DMF), N-methylformamide, formamide, acetonitrile, dimethylacetamide, propylene carbonate, ethylene carbonate, n-methylpyrrolidone, dimethylsulfoxide, or a combination thereof. In some examples, the solvent comprises dimethylformamide, dimethylacetamide, acetonitrile, or a combination thereof.

[0012] In some examples, depositing the dispersion comprises printing, spin coating, drop casting, zone casting, dip coating, blade coating, spraying, vacuum filtration, slot die coating, curtain coating, or a combination thereof. In some examples, depositing the dispersion comprises spin coating.

[0013] In some examples, the method further includes removing the composite film from the substrate. In some examples, the method further includes producing a plurality of nanostructured metal oxide crystals. In some examples, the method includes removing the ligand and / or capping agent from the plurality of nanostructured metal oxide crystals such that the plurality of nanostructured metal oxide crystals are substantially free of the ligand and / or capping material.

[0014] Also disclosed herein is a device comprising any of the composite films described herein, which may include a fuel cell, an electrolyzer, a proton exchange electrolyzer, or a battery. In some examples, the device comprises a proton exchange membrane fuel cell (PEMFC). In some examples, the device is operated at a temperature of 25°C or more, 50°C or more, 100°C or more, 200°C or more, or 300°C or more.

[0015] Also disclosed herein is a method of using any of the composite films described herein, comprising using the composite film as a proton exchange membrane, an ion exchange membrane, a hydrogen separation membrane, a solid electrolyte, or a combination thereof. Also disclosed herein is a method of using any of the composite films described herein, comprising using the composite film in a fuel cell. In some examples, the method comprises using the composite film as a proton exchange membrane in a proton exchange membrane fuel cell (PEMFC). In some examples, the method is performed at a temperature of 25° C. or more, 50° C. or more, 100° C. or more, 200° C. or more, or 300° C. or more.

[0016] Also disclosed herein is a method of use of any of the composite films described herein, comprising using the composite film in electrolysis, in reversible electrodialysis, in a chlor-alkali system, or a combination thereof.

[0017] Additional advantages of the disclosed compositions and methods will be set forth in part in the description which follows and in part will be apparent from the description. The advantages of the disclosed compositions and methods will be realized and attained by means of the elements and combinations particularly pointed out in the appended claims. It is to be understood that both the foregoing general description and the following detailed description are merely illustrative and are not restrictive of the disclosed devices and methods, as claimed.

[0018] The details of one or more embodiments of the invention are set forth in the accompanying drawings and the description below. Other features, objects, and advantages of the invention will become apparent from the following description, drawings, and claims.

[0019] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate several aspects of the present disclosure and, together with the description, serve to explain the principles of the present disclosure. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is an Ellingham structure showing the oxidation of cerium oxide. [Diagram 2] FIG. 2 is an Ellingham structure showing the oxidation of cerium oxide. [Diagram 3] FIG. 3 is a scanning transmission electron microscope (SEM) image of CeO2 nanocrystals. [Figure 4] Figure 4 shows the X-ray diffraction of CeO2 nanocrystals. [Diagram 5] FIG. 5 is a scanning microscope image of a composite film containing a 50:50 nanocrystal:polymer volume fraction. [Figure 6] FIG. 6 is a scanning microscope image of a composite film containing a 50:50 nanocrystal:polymer volume fraction. [Figure 7] FIG. 7 shows the ionic conductivity of the CeO2 only film. [Figure 8] FIG. 8 shows the ionic conductivity of the PEO-only film. [Figure 9] FIG. 9 shows the ionic conductivity of the CeO2-PEO composite film. [Figure 10] FIG. 10 shows the ionic conductivity of the CeO2-polybenzimidazole composite film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The compositions, devices and methods described herein can be understood more readily by reference to the following detailed description of certain aspects of the disclosed subject matter and examples contained herein.

[0022] Before the present compositions, devices, and methods are disclosed and described, it is to be understood that the embodiments described below are not limited to particular synthetic methods or to particular reagents, as these may vary. It is also to be understood that the terminology used herein is for the purpose of describing particular embodiments only, and is not intended to be limiting.

[0023] Also throughout this specification, various publications are referenced. The disclosures of these publications in their entireties are hereby incorporated by reference into this application in order to more fully describe the state of the art to which the disclosed subject matter pertains. The references disclosed are also individually specifically incorporated by reference into this specification for the material contained therein that is discussed in the sentence in which the reference is relied upon.

[0024] General definition In this specification and the claims that follow, reference will be made to a number of terms that shall be defined to have the following meanings:

[0025] Throughout the description and claims of this specification, the word "comprise" and other forms of the word, such as "comprising" and "comprises," are not intended to include, but are not limited to, other additives, components, integers or steps.

[0026] As used in the description and the appended claims, the singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise. Thus, for example, reference to "a composition" includes mixtures of two or more such compositions, reference to "the compound" includes mixtures of two or more such compounds, reference to "an agent" includes mixtures of two or more such agents, etc.

[0027] "Optional" or "optionally" means that the subsequently described event or circumstance may or may not occur, and that the description includes instances in which the event or circumstance occurs and instances in which the said event or circumstance does not occur.

[0028] Composite Film Disclosed herein is a composite film comprising a plurality of nanostructured metal oxide crystals dispersed within an ion-conducting polymer phase (e.g., a proton-conducting polymer phase). As used herein, "nanostructured" refers to any structure having one or more nano-dimensional features. A nano-dimensional feature can be any feature having at least one dimension that is sized 20 nanometers (nm) or less (e.g., 10 nm or less). For example, a nano-dimensional feature can include nanowires, nanotubes, nanoparticles, nanopores, and the like, or combinations thereof. Thus, each of the plurality of nanostructured metal oxide crystals can include, for example, nanowires, nanotubes, nanoparticles, nanopores, or combinations thereof. In some examples, each of the plurality of nanostructured metal oxide crystals can include modified metal oxide crystals that are not nano-dimensional but have nanowires, nanotubes, nanoparticles, nanopores, or combinations thereof.

[0029] As used herein, a "phase" generally refers to a region of a material having a substantially uniform composition that is a distinct physically separate part of a heterogeneous system. The term "phase" does not imply that the materials that make up the phase are chemically pure substances, but merely that the chemical and / or physical properties of the materials that make up the phase are essentially uniform throughout the material, and that the chemical and / or physical properties are significantly different from the chemical and / or physical properties of another phase within the material. Examples of physical properties include density, thickness, aspect ratio, specific surface area, porosity, and dimensionality. Examples of chemical properties include chemical composition.

[0030] The nanostructured metal oxide crystals can, for example, have a large average total surface area, comprise a reducible metal oxide, have a low oxygen vacancy defect formation energy, a high isoelectric point, are substantially electronically insulating, have a high surface oxygen vacancy concentration, or a combination thereof.

[0031] The nanostructured metal oxide crystals may include any suitable metal oxide, optionally doped with one or more dopants. For example, the nanostructured metal oxide crystals may include a reducible metal oxide. As used herein, a "reducible metal oxide" generally refers to an oxide of a metal, including a metal that can hold different valence states (e.g., one or more of +1, +2, +3, +4, +5, etc.) in bulk form or as defect states on the surface of the metal oxide. For example, a reducible metal oxide includes a metal oxide in which the curve of the metal oxide is lower than the equilibrium of hydrogen, oxygen, and water in the Ellingham structure, which shows the oxidation of metal oxides with the same cation components, suggesting that the metal oxide is oxidized in the presence of water vapor to form adsorbed hydrogen or hydrogen gas with the simultaneous reduction of water, as shown for cerium oxide in Figures 1 and 2.

[0032] In some examples, the nanostructured metal oxide crystals can include niobium oxide, titanium oxide, silicon oxide, tungsten oxide, zirconium oxide, hafnium oxide, magnesium oxide, vanadium oxide, iron oxide, chromium oxide, manganese oxide, nickel oxide, cerium oxide, gadolinium oxide, samarium oxide, or combinations thereof. In some examples, the nanostructured metal oxide crystals can include niobium oxide, titanium oxide, tungsten oxide, hafnium oxide, vanadium oxide, iron oxide, chromium oxide, manganese oxide, nickel oxide, cerium oxide, gadolinium oxide, samarium oxide, or combinations thereof. In some examples, the nanostructured metal oxide crystals can include cerium oxide. In some examples, the nanostructured metal oxide crystals can include cerium oxide doped with one or more dopants, such as one or more aliovalent acceptor dopants (e.g., trivalent acceptor dopants). In some examples, the plurality of nanostructured metal oxide crystals may comprise gadolinium doped cerium oxide, samarium doped cerium oxide, or a combination thereof. The plurality of nanostructured metal oxide crystals may in some examples be substantially free of ligands and / or capping materials.

[0033] The plurality of nanostructured metal oxide crystals can include crystals of any shape (e.g., spheres, rods, squares, ellipses, triangles, polygons, etc.). In some examples, the plurality of nanostructured metal oxide crystals can have an isotropic shape. In some examples, the plurality of nanostructured metal oxide crystals can have an anisotropic shape. In some examples, the shape of the plurality of nanostructured metal oxide crystals can be selected to expose a particular facet. In certain examples, the shape of the plurality of nanostructured metal oxide crystals can be selected to expose a (100) facet.

[0034] In some examples, each of the plurality of nanostructured metal oxide crystals is 20 nm or less (e.g., 19.5 nm or less, 19 nm or less, 18.5 nm or less, 18 nm or less, 17.5 nm or less, 17 nm or less, 16.5 nm or less, 16 nm or less, 15.5 nm or less, 15 nm or less, 14.5 nm or less, 14 nm or less, 13.5 nm or less, 13 nm or less, 12.5 nm or less, 12 nm or less, 11.5 nm or less, 11 nm or less, 10.5 nm or less, 10 nm or less, 9.75 nm or less, 9.5 nm or less, 9.25 nm or less, 9 nm or less, 8.75 nm or less, In some embodiments, the nanoparticles may have at least one dimension that is sized such that the nanoparticles have a size of 8.5 nm or less, 8.25 nm or less, 8 nm or less, 7.75 nm or less, 7.5 nm or less, 7.25 nm or less, 7 nm or less, 6.75 nm or less, 6.5 nm or less, 6.25 nm or less, 6 nm or less, 5.75 nm or less, 5.5 nm or less, 5.25 nm or less, 5 nm or less, 4.75 nm or less, 4.5 nm or less, 4.25 nm or less, 4 nm or less, 3.75 nm or less, 3.5 nm or less, 3.25 nm or less, 3 nm or less, 2.75 nm or less, 2.5 nm or less, 2.25 nm or less, or 2 nm or less. In some examples, each of the plurality of nanostructured metal oxide crystals is 1 nm or greater (e.g., 1.25 nm or greater, 1.5 nm or greater, 1.75 nm or greater, 2 nm or greater, 2.25 nm or greater, 2.5 nm or greater, 2.75 nm or greater, 3 nm or greater, 3.25 nm or greater, 3.5 nm or greater, 3.75 nm or greater, 4 nm or greater, 4.25 nm or greater, 4.5 nm or greater, 4.75 nm or greater, 5 nm or greater, 5.25 nm or greater, 5.5 nm or greater, 5.75 nm or greater, 6 nm or greater, 6.25 nm or greater, 6.5 nm or greater, 6.75 nm or greater, 7 nm or greater, 7.25 nm or greater, 7.5 nm or greater, 7. In some embodiments, the nanoparticles may have at least one dimension that is a size of 0.75 nm or more, 8 nm or more, 8.25 nm or more, 8.5 nm or more, 8.75 nm or more, 9 nm or more, 9.25 nm or more, 9.5 nm or more, 9.75 nm or more, 10 nm or more, 10.5 nm or more, 11 nm or more, 11.5 nm or more, 12 nm or more, 12.5 nm or more, 13 nm or more, 13.5 nm or more, 14 nm or more, 14.5 nm or more, 15 nm or more, 15.5 nm or more, 16 nm or more, 16.5 nm or more, 17 nm or more, 17.5 nm or more, 18 nm or more, 18.5 nm or more, or 19 nm or more.Each of the plurality of nanostructured metal oxide crystals can have at least one dimension that ranges in size from any of the minimum values ​​listed above to any of the maximum values ​​listed above. For example, each of the plurality of nanostructured metal oxide crystals can have at least one dimension that is sized between 1 nm and 20 nm (e.g., 1 nm to 10 nm, 10 nm to 20 nm, 1 nm to 5 nm, 5 nm to 10 nm, 10 nm to 15 nm, 15 nm to 20 nm, 1 nm to 4 nm, 4 nm to 7 nm, 7 nm to 10 nm, 10 nm to 13 nm, 13 nm to 16 nm, 16 nm to 20 nm, 1 nm to 15 nm, 2 nm to 20 nm, or 2 nm to 9 nm). As used herein, the size of at least one dimension of each of the plurality of nanostructured metal oxide crystals is determined by electron microscopy.

[0035] In some examples, the nanostructured metal oxide crystals can have an average particle size. "Average particle size" and "statistical mean particle size" are used interchangeably herein and generally refer to the statistical average particle size of the particles (or crystals) in a population of particles (or crystals). For example, the average particle size for a plurality of particles having a substantially spherical shape can include the average diameter of the plurality of particles. For a particle having a substantially spherical shape, the diameter of the particle can refer to, for example, the hydrodynamic diameter. As used herein, the hydrodynamic diameter of the particle can refer to the largest linear distance between two points on the surface of the particle. For anisotropic particles, the average particle size can refer to, for example, the average largest dimension of the particle (e.g., the length of a rod-shaped particle, the diagonal of a cube-shaped particle, the bisector of a triangular-shaped particle, etc.). For anisotropic particles, the average particle size can refer to, for example, the hydrodynamic size of the particle. The statistical mean particle size can be measured using methods known in the art, such as scanning electron microscopy, transmission electron microscopy, and / or dynamic light scattering evaluation. As used herein, average particle size is determined by electron microscopy.

[0036] The plurality of nanostructured metal oxide crystals may be, for example, 1 nm or greater (e.g., 1.25 nm or greater, 1.5 nm or greater, 1.75 nm or greater, 2 nm or greater, 2.25 nm or greater, 2.5 nm or greater, 2.75 nm or greater, 3 nm or greater, 3.25 nm or greater, 3.5 nm or greater, 3.75 nm or greater, 4 nm or greater, 4.25 nm or greater, 4.5 nm or greater, 4.75 nm or greater, 5 nm or greater, 5.25 nm or greater, 5.5 nm or greater, 5.75 nm or greater, 6 nm or greater, 6.25 nm or greater, 6.5 nm or greater, 6.75 nm or greater, 7 nm or greater, 7.25 nm or greater, 7.5 nm or greater, 7.75 nm or greater, 8 nm or greater, 7.25 nm or greater, 8.5 nm or greater, 8.75 nm or greater, 9 nm or greater, 9.25 nm or greater or greater, 9.5 nm or greater, 9.75 nm or greater, 10 nm or greater, 10.5 nm or greater, 11 nm or greater, 11.5 nm or greater, 12 nm or greater, 12.5 nm or greater, 13 nm or greater, 13.5 nm or greater, 14 nm or greater, 14.5 nm or greater, 15 nm or greater, 15.5 nm or greater, 16 nm or greater, 16.5 nm or greater, 17 nm or greater, 17.5 nm or greater, 18 nm or greater, 18.5 nm or greater, 19 nm or greater, 19.5 nm or greater, 20 nm or greater, 21 nm or greater, 22 nm or greater, 23 nm or greater, 24 nm or greater, 25 nm or greater, 30 nm or greater, 35 nm or greater, 40 nm or greater, 45 nm or greater, 50 nm or greater, 60 nm or greater, 70 nm or greater, or 80 nm or greater.

[0037] In some examples, the nanostructured metal oxide crystals are 100 nm or less (e.g., 90 nm or less, 80 nm or less, 70 nm or less, 60 nm or less, 50 nm or less, 45 nm or less, 40 nm or less, 35 nm or less, 30 nm or less, 25 nm or less, 24 nm or less, 23 nm or less, 22 nm or less, 21 nm or less, 20 nm or less, 19.5 nm or less, 19 nm or less, 18.5 nm or less, 18 nm or less, 17.5 nm or less, 17 nm or less, 16.5 nm or less, 16 nm or less, 15.5 nm or less, 15 nm or less, 14.5 nm or less, 14 nm or less, 13.5 nm or less, 13 nm or less, 12.5 nm or less, 12 nm or less, 11.5 nm or less, 11 nm or less, 1 In some embodiments, the nanoparticles may have an average particle size of 0.5 nm or less, 10 nm or less, 9.75 nm or less, 9.5 nm or less, 9.25 nm or less, 9 nm or less, 8.75 nm or less, 8.5 nm or less, 8.25 nm or less, 8 nm or less, 7.75 nm or less, 7.5 nm or less, 7.25 nm or less, 7 nm or less, 6.75 nm or less, 6.5 nm or less, 6.25 nm or less, 6 nm or less, 5.75 nm or less, 5.5 nm or less, 5.25 nm or less, 5 nm or less, 4.75 nm or less, 4.5 nm or less, 4.25 nm or less, 4 nm or less, 3.75 nm or less, 3.5 nm or less, 3.25 nm or less, 3 nm or less, 2.75 nm or less, 2.5 nm or less, 2.25 nm or less, or 2 nm or less.

[0038] The average particle size of the plurality of nanostructured metal oxide nanocrystals can range from any of the minimum values ​​listed above to any of the maximum values ​​listed above. The plurality of nanostructured metal oxide nanocrystals can have an average particle size ranging from, for example, 1 nm to 100 nm (e.g., 1 nm to 50 nm, 50 nm to 100 nm, 1 nm to 20 nm, 20 nm to 40 nm, 40 nm to 60 nm, 60 nm to 80 nm, 80 nm to 100 nm, 1 nm to 40 nm, 1 nm to 30 nm, 1 nm to 20 nm, 1 nm to 10 nm, 10 nm to 20 nm, 1 nm to 5 nm, 5 nm to 10 nm, 10 nm to 15 nm, 15 nm to 20 nm, 1 nm to 4 The polymer may have an average particle size of 1 nm, 4 nm to 7 nm, 7 nm to 10 nm, 10 nm to 13 nm, 13 nm to 16 nm, 16 nm to 20 nm, 1 nm to 15 nm, 5 nm to 20 nm, 5 nm to 15 nm, 2 nm to 10 nm, 1 nm to 9.5 nm, 1 nm to 9 nm, 1 nm to 8.5 nm, 1 nm to 8 nm, 1 nm to 7.5 nm, 1 nm to 7 nm, 1 nm to 6.5 nm, 1 nm to 6 nm, 1 nm to 5.5 nm or 2 nm to 9 nm).

[0039] In some instances, the nanostructured metal oxide crystals may be substantially monodisperse. "Monodisperse" and "homogeneous particle size distribution" as used herein generally describe a population of particles where the particles are all the same or nearly the same size. As used herein, a monodisperse distribution refers to a particle distribution where 80% of the distribution (e.g., 85% of the distribution, 90% of the distribution, or 95% of the distribution) is within 25% of the median particle size (e.g., within 20% of the average particle size, within 15% of the average particle size, 10% of the average particle size, or within 5% of the average particle size).

[0040] In some examples, the plurality of nanostructured metal oxide crystals can include cerium oxide, and each of the plurality of nanostructured metal oxide crystals can have at least one dimension that is between 1 nm and 5 nm in size. In some examples, the plurality of nanostructured metal oxide crystals can include cerium oxide, have an average particle shape that is substantially isotropic, and can have an average grain size between 1 nm and 10 nm.

[0041] In some examples, the plurality of nanostructured metal oxide crystals can include cerium oxide, each of the plurality of nanostructured metal oxide crystals can have at least one dimension that is between 1 nm and 5 nm in size, and the plurality of nanostructured metal oxide crystals can have a shape that exposes (100) facets, such as a cube or platelet shape. In some examples, the plurality of nanostructured metal oxide crystals can include cerium oxide, have an average grain shape that exposes (100) facets, and have an average grain size of between 1 nm and 10 nm.

[0042] The ion-conducting polymer phase can, for example, have high ion mobility, be substantially thermally stable, be substantially mechanically stable, have a low glass transition temperature, have high segmented chain mobility, have a low temperature of crystallization, be amorphous, or a combination thereof.

[0043] In some examples, the ion-conducting polymer phase can include a proton-conducting polymer phase that can, for example, have high ionic mobility, be substantially thermally stable, be substantially mechanically stable, have a low glass transition temperature, have high segmented chain mobility, have a low temperature of crystallization, be amorphous, or a combination thereof.

[0044] The proton conducting polymer phase can include, for example, a polymer electrolyte such as those known in the art. For example, the proton conducting polymer phase may be formed by the following methods: Kreuer, "Ion Conducting Membranes for Fuel Cells and other Electrochemical Devices," Chem. Mater., 2014, 26, 361-380;Hickner et al. "Alternate Polymer Systems for Proton Exchange Membranes (PEMs)," Chem. Rev., 2004, 104, 4587-4612;Cheng et al. "Gel Polymer Electrolytes for Electrochemical Energy Storage," Adv. Ener. Mat., 2018, 8, 1702184;Meyer, "Polymer Electrolytes for Lithium-Ion Batteries," Adv. Mat., 1998, 10, 439-448;Hallinan et al. "Polymer Electrolytes," Annu. Rev. Mater. Res 2013, 43, 503-525; and Mindemark et al. "Beyond PEO - Alternate host materials for Li conducting solid polymer electrolytes," Progress in Polymer Science 2018, 81, 114-143, each of which is hereby incorporated by reference in its entirety for its teachings on polymers. In some examples, the proton conducting polymer phase can include any polymer that includes one or more basic functional groups (e.g., ether, pyridine, sulfonate, etc.).

[0045] The proton conducting polymer phase can include, for example, polyether, polysulfonate, polysulfone, poly(imidazole), triazole, benzimidazole, polyester, polycarbonate, polymer derived from pyridine monomer, derivatives thereof, or combinations thereof. In some examples, the proton conducting polymer phase can include polyether or derivatives thereof. In some examples, the proton conducting polymer phase can include polyethylene oxide, polyetherpyridine, polyetheretherketone (PEEK), polytetrahydrofuran, polyvinylbutyral, polybenzimidazole, derivatives thereof, or combinations thereof. In certain examples, the proton conducting polymer can include polyethylene oxide, polytetrahydrofuran, derivatives thereof, or combinations thereof.

[0046] In some examples, the plurality of nanostructured metal oxide crystals can include cerium oxide, each of the plurality of nanostructured metal oxide crystals can have at least one dimension that is sized between 1 nm and 5 nm, and the proton conducting polymer can include polyethylene oxide, polytetrahydrofuran, derivatives thereof, or combinations thereof. In some examples, the plurality of nanostructured metal oxide crystals can include cerium oxide, have an average particle shape that is substantially isotropic, and have an average grain size between 1 nm and 10 nm, and the proton conducting polymer can include polyethylene oxide, polytetrahydrofuran, derivatives thereof, or combinations thereof.

[0047] The composite film may, for example, comprise 20% or more by volume of the composite film (e.g., 21% or more, 22% or more, 23% or more, 24% or more, 25% or more, 26% or more, 27% or more, 28% or more, 29% or more, 30% or more, 31% or more, 32% or more, 33% or more, 34% or more, 35% or more, 36% or more, 37% or more, 38% or more, 39% or more, 40% or more, 41% or more, 42% or more, 43% or more, 44% or more, 45% or more, 46% or more, 47% or more, 48% or more, 49% or more, 50% or more, 51% or more, 52% or more). , 53% or more, 54% or more, 55% or more, 56% or more, 57% or more, 58% or more, 59% or more, 60% or more, 61% or more, 62% or more, 63% or more, 64% or more, 65% or more, 66% or more, 67% or more, 68% or more, 69% or more, 70% or more, 71% or more, 72% or more, 73% or more, 74% or more, 75% or more, 76% or more, 77% or more, 78% or more, 79% or more, 80% or more, 81% or more, 82% or more, 83% or more, 84% or more, or 85% or more).

[0048] In some examples, the composite film comprises 90% or less by volume of the composite film (e.g., 89% or less, 88% or less, 87% or less, 86% or less, 85% or less, 84% or less, 83% or less, 82% or less, 81% or less, 80% or less, 79% or less, 78% or less, 77% or less, 76% or less, 75% or less, 74% or less, 73% or less, 72% or less, 71% or less, 70% or less, 69% or less, 68% or less, 67% or less, 66% or less, 65% or less, 64% or less, 63% or less, 62% or less, 61% or less, 60% or less, 59% or less, 58% or less, 60 ... %, 57% or less, 56% or less, 55% or less, 54% or less, 53% or less, 52% or less, 51% or less, 50% or less, 49% or less, 48% or less, 47% or less, 46% or less, 45% or less, 44% or less, 43% or less, 42% or less, 41% or less, 40% or less, 39% or less, 38% or less, 37% or less, 36% or less, 35% or less, 34% or less, 33% or less, 32% or less, 31% or less, 30% or less, 29% or less, 28% or less, 27% or less, 26% or less, or 25% or less.

[0049] The amount of the nanostructured metal oxide crystals in the composite film can range from any of the minimum values ​​listed above to any of the maximum values ​​listed above. For example, the composite film can include 20% to 90% (e.g., 20% to 55%, 55% to 90%, 20% to 30%, 30% to 40%, 40% to 50%, 50% to 60%, 60% to 70%, 70% to 80%, 80% to 90%, 30% to 90%, 20% to 80%, 30% to 80%, 30% to 70%, 20% to 70%, 30% to 60%, 20% to 50%, or 30% to 50%) of the nanostructured metal oxide crystals by volume of the composite film.

[0050] In some examples, the nanostructured metal oxide crystals may include cerium oxide, and each of the nanostructured metal oxide crystals may have at least one dimension that is between 1 nm and 5 nm in size; the proton conducting polymer may include polyethylene oxide, polytetrahydrofuran, a derivative thereof, or a combination thereof; the composite film may include 20% to 70% by volume of the nanostructured metal oxide crystals. In some examples, the nanostructured metal oxide crystals may include cerium oxide, have an average particle shape that is substantially isotropic, and have an average grain size between 1 nm and 10 nm; the proton conducting polymer may include polyethylene oxide, polytetrahydrofuran, a derivative thereof, or a combination thereof; the composite film may include 20% to 70% by volume of the nanostructured metal oxide crystals.

[0051] The composite film may be, for example, 100 nanometers (nm) or more (e.g., 150 nm or more, 200 nm or more, 250 nm or more, 300 nm or more, 350 nm or more, 400 nm or more, 450 nm or more, 500 nm or more, 600 nm or more, 700 nm or more, 800 nm or more, 900 nm or more, 1 micrometer (micron, μm) or more, 2 μm or more, 3 μm or more, 4 μm or more, 5 μm or more, 6 μm or more, 7 μm or more, 8 μm or more, 9 μm or more, m or more, 10 μm or more, 15 μm or more, 20 μm or more, 25 μm or more, 30 μm or more, 35 μm or more, 40 μm or more, 45 μm or more, 50 μm or more, 60 μm or more, 70 μm or more, 80 μm or more, 90 μm or more, 100 μm or more, 125 μm or more, 150 μm or more, 175 μm or more, 200 μm or more, 225 μm or more, 250 μm or more, 300 μm or more, 350 μm or more, or 400 μm or more). In some examples, the composite film has a thickness of 500 μm or less (e.g., 450 μm or less, 400 μm or less, 350 μm or less, 300 μm or less, 250 μm or less, 225 μm or less, 200 μm or less, 175 μm or less, 150 μm or less, 125 μm or less, 100 μm or less, 90 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, 50 μm or less, 45 μm or less, 40 μm or less, 35 μm or less, 30 μm or less, 25 μm or less). The composite film may have an average thickness of 0.1 to 1.5 μm, 0.2 to 1.5 μm, 0.3 to 1.5 μm, 0.4 to 0.5 μm, 0.5 to 1.5 μm, 0.6 to 0.7 μm, 0.7 to 0.8 μm, 0.8 to 0.9 μm, 0.9 to 1.5 ... For example, the composite film can have an average thickness of 100 nm to 500 μm (e.g., 500 nm to 500 μm, 1 μm to 500 μm, 10 μm to 500 μm, 10 μm to 400 μm, 10 μm to 300 μm, 10 μm to 200 μm, or 10 μm to 100 μm).The average thickness of the composite film can be measured by methods known in the art, such as profilometry, cross-sectional electron microscopy, atomic force microscopy (AFM), ellipsometry, veneer calipers, micrometer gauges, or combinations thereof.

[0052] The nanostructured metal oxide crystals can, for example, exhibit preferential adsorption of water at the surface and dissociation of water at defect sites to retain water and generate mobile protons at ambient temperatures or above (e.g., 25° C. or above, 100° C. or above), e.g., at higher temperatures (e.g., 100° C. or above), while the proton conducting polymer phase can, for example, provide a conductive pathway for protons, thereby dramatically increasing the absolute proton conductivity of the composite (e.g., as described by Meng et. al., “Review: recent progress in low temperature proton conducting ceramics,” Journal of Materials Science 2019, 54, 9291-9312, which is hereby incorporated by reference in its entirety for its teachings on metal oxides).

[0053] The composite film is, for example, 10 -8 S / cm or more (e.g., 1×10 -7 S / cm or more, 1×10 -6 S / cm or more, 1×10 -5 S / cm or more, 1×10 -4 S / cm or more, 1×10 -3 S / cm or more, 0.01 S / cm or more, or 0.1 S / cm or more) at a temperature of 25° C. or more (e.g., 30° C. or more, 35° C. or more, 40° C. or more, 45° C. or more, 50° C. or more, 60° C. or more, 70° C. or more, 80° C. or more, 90° C. or more, 100° C. or more, 150° C. or more, 200° C. or more, 250° C. or more, 300° C. or more, 350° C. or more, 400° C. or more, 450° C. or more, 500° C. or more, or 550° C. or more). In some examples, the composite film can have a proton conductivity of 1 S / cm or less (e.g., 0.1 S / cm or less, 0.01 S / cm or less, 1×10 -3S / cm or less, 1×10 -4 S / cm or less, 1×10 -5 S / cm or less, 1×10 -6 S / cm or less, or 1×10 -7 The composite film may have a proton conductivity of 100 S / cm or less at a temperature of 25° C. or greater (e.g., 30° C. or greater, 35° C. or greater, 40° C. or greater, 45° C. or greater, 50° C. or greater, 60° C. or greater, 70° C. or greater, 80° C. or greater, 90° C. or greater, 100° C. or greater, 150° C. or greater, 200° C. or greater, 250° C. or greater, 300° C. or greater, 350° C. or greater, 400° C. or greater, 450° C. or greater, 500° C. or greater, or 550° C. or greater). The proton conductivity of the composite film may range from any of the minimum values ​​listed above to any of the maximum values ​​listed above. For example, the composite film may have a proton conductivity of 100 S / cm or greater at a temperature of 25° C. or greater (e.g., 30° C. or greater, 350° C. or greater, 400° C. or greater, 450° C. or greater, 500° C. or greater, or 550° C. or greater). -8 S / cm to 1S / cm (e.g., 10 -8 S / cm~10 -4 S / cm, 10 -4 S / cm~1S / cm, 10 -8 S / cm~10 -6 S / cm, 10 -6 S / cm~10 -4 S / cm, 10 -4 S / cm~10 -2 S / cm, 10 -2 S / cm~1S / cm, 10 -6 S / cm~1S / cm, 10 -4 The proton conductivity may be from 25°C to 600°C (e.g., 25°C to 300°C, 300°C to 600°C, 25°C to 100°C, 100°C to 350°C, 350°C to 600°C, 100°C to 200°C, 200°C to 300°C, 300°C to 400°C, 400°C to 500°C, 500°C to 600°C, 100°C to 600°C, 100°C to 450°C, or 100°C to 300°C).

[0054] The composite film can, in some instances, form a free-standing membrane. In some instances, the composite film is supported by a substrate. Examples of suitable substrates include, but are not limited to, polymers (e.g., porous polymers), fiberglass, glass, quartz, silicon, and combinations thereof.

[0055] In some examples, the plurality of nanostructured metal oxide crystals can include cerium oxide, and each of the plurality of nanostructured metal oxide crystals can have at least one dimension that is between 1 nm and 5 nm in size; the proton conducting polymer can include polyethylene oxide, polytetrahydrofuran, derivatives thereof, or combinations thereof; and the composite film can be heated to 100° C. or higher at a temperature of 25° C. or higher (e.g., 100° C. or higher). -8 In some examples, the plurality of nanostructured metal oxide crystals can include cerium oxide, have an average particle shape that is substantially isotropic, and have an average particle size of 1 nm to 10 nm; the proton conducting polymer can include polyethylene oxide, polytetrahydrofuran, derivatives thereof, or combinations thereof; and the composite film can have a proton conductivity of 10 S / cm or more at a temperature of 25° C. or more (e.g., 100° C. or more). -8 The proton conductivity may be 1.0 S / cm or more.

[0056] In some instances, the plurality of nanostructured metal oxide crystals are intimately mixed with the proton conducting polymer phase within the composite film. In some instances, the plurality of nanostructured metal oxide crystals and the proton conducting polymer phase do not phase separate within the composite film.

[0057] Manufacturing method Also disclosed herein is a method of making any of the composite films described herein, comprising dispersing a plurality of nanostructured metal oxide crystals and a polymer comprising a proton conducting polymer phase in a solvent, thereby forming a dispersion; and depositing the dispersion onto a substrate, thereby forming a composite film. In some examples, the method can further comprise removing the composite film from the substrate.

[0058] Examples of solvents include, but are not limited to, tetrahydrofuran (THF), dimethylformamide (DMF), N-methylformamide, formamide, acetonitrile, dimethylacetamide, propylene carbonate, ethylene carbonate, n-methylpyrrolidone, dimethylsulfoxide, or combinations thereof. In some examples, the solvent can include dimethylformamide, dimethylacetamide, acetonitrile, or combinations thereof.

[0059] The step of depositing the dispersion can include, for example, printing, spin coating, drop casting, zone casting, dip coating, blade coating, spraying, vacuum filtration, slot die coating, curtain coating, or a combination thereof. In some examples, the step of depositing the dispersion can include spin coating.

[0060] In some examples, the method can further include producing a plurality of nanostructured metal oxide crystals (e.g., using a colloidal method). In some examples, the method can further include removing ligands and / or capping agents from the plurality of nanostructured metal oxide crystals such that the plurality of nanostructured metal oxide crystals are substantially free of ligands and / or capping materials.

[0061] How to use Also provided herein are methods of using any of the composite films described herein. For example, the composite films described herein can be used in electrolysis, in reversible electrodialysis, in chlor-alkali systems, or combinations thereof. In some examples, the composite films described herein can be used as proton exchange membranes, ion exchange membranes, hydrogen separation membranes, solid electrolytes, or combinations thereof. In some examples, the composite films described herein can be used in fuel cells. The composite films can be used, for example, as proton exchange membranes in proton exchange membrane fuel cells (PEMFCs). In some examples, the method of use can be carried out at a temperature of 25° C. or greater (e.g., 30° C. or greater, 35° C. or greater, 40° C. or greater, 45° C. or greater, 50° C. or greater, 60° C. or greater, 70° C. or greater, 80° C. or greater, 90° C. or greater, 100° C. or greater, 150° C. or greater, 200° C. or greater, 250° C. or greater, 300° C. or greater, 350° C. or greater, 400° C. or greater, 450° C. or greater, 500° C. or greater, or 550° C. or greater).

[0062] In some examples, the composite films described herein can be used in various articles or devices of manufacture, including fuel cells, electrolyzers, proton exchange electrolyzers, and batteries. Such articles and devices of manufacture can be manufactured by methods known in the art. In some examples, the articles or devices of manufacture can operate at temperatures of 25° C. or higher (e.g., 30° C. or higher, 35° C. or higher, 40° C. or higher, 45° C. or higher, 50° C. or higher, 60° C. or higher, 70° C. or higher, 80° C. or higher, 90° C. or higher, 100° C. or higher, 150° C. or higher, 200° C. or higher, 250° C. or higher, 300° C. or higher, 350° C. or higher, 400° C. or higher, 450° C. or higher, 500° C. or higher, or 550° C. or higher).

[0063] The following examples are intended to further illustrate certain aspects of the methods and compounds described herein and are not intended to limit the scope of the claims of this application. EXAMPLES

[0064] The following examples are set forth below to illustrate the methods and results according to the disclosed subject matter. These examples are not intended to encompass all aspects of the subject matter disclosed herein, but rather to illustrate representative methods, compositions and results. These examples are not intended to exclude equivalents and variations of the present invention that are obvious to those skilled in the art.

[0065] Efforts have been made to ensure accuracy with respect to numbers (e.g., amounts, temperature, etc.), but some errors and deviations should be accounted for. Unless otherwise indicated, parts are parts by weight, temperature is in °C or is at ambient temperature, and pressure is at or near atmospheric. Numerous variations and combinations of reaction conditions, e.g., component concentrations, temperatures, pressures, and other reaction ranges and conditions, exist and can be used to optimize the purity and yield of the products obtained from the described processes. Only reasonable and routine experimentation is required to optimize such process conditions.

[0066] [Example 1] One of the defining properties of nanomaterials is their large surface-to-volume ratio. This simple but important property transforms the material's properties into those dominated by the surface, allowing for a large deviation in overall properties from their bulk counterparts. A property that interfaces boost within the context of ion transport materials is the mid-temperature (300°C-100°C) proton conduction in porous nanocrystalline metal oxide systems such as cerium oxide, zirconium oxide, and titanium oxide. Previous studies of metal oxides have established these materials as poor proton conductors in bulk form. However, when nanosized and made porous, these same materials can exhibit significant proton conductivity under humid conditions; this deviation can be attributed to the change in interface density going from bulk crystalline size to nanocrystalline size, and the introduction of a solid-vapor interface, allowing for ion transport.

[0067] The discovery of intermediate temperature proton conduction for these materials is in line with the current interest in operating proton exchange membrane fuel cells (PEMFCs) and electrolysis at high temperatures. The push to higher temperatures is rationalized by three main reasons. First, there is an increase in electrochemical efficiency and catalytic rate at high temperatures, which can be particularly important for the slow oxygen reduction or oxygen evolution reactions. Second, fuel cells operating at higher temperatures will be able to produce more efficient proton conduction reactions by reducing CO and H 2 They may be more tolerant of impurities in the gas stream, such as S, which can cause poisoning of catalysts at the anode and cathode. Third, the device design can be simplified by eliminating the need for external thermal management and complex water management. However, the operating temperature of current PEMFCs is limited by the operating temperature of the proton exchange membranes (mostly Nafion), which dehydrate at temperatures above 80 °C, leading to a significant loss of proton conductivity above 80 °C. Attempts to widen the temperature window for operation have included the use of new proton conducting materials, e.g., CsHSO 4 , BaZrO 3 and BaCeO 3 These have resulted in solid acids such as ceramics; sol-gel silica glasses; metal-organic frameworks; silica phosphotungstic acid hybrids; and polymer-phosphate hybrids such as physical mixtures of polybenzimidazoles or polyetherpyridines with phosphoric acid or polyphosphoric acid.

[0068] Once an understanding of the mid-temperature proton conduction exhibited by the porous nanocrystalline structure was established, further investigations revealed that the proton conductivity may not be limited by the formation of protons due to dissociation of water on the nanocrystalline surface, but rather by the lack of a matrix through which protons can be conducted. At high temperatures above 100°C, the amount of adsorbed water in the porous nanocrystalline structure is estimated to be at most one or two layers thick and decreases with increasing temperature. A suitable ion-conducting matrix can be introduced to boost the ion conductivity in the system. The final product is an inorganic-organic material, such as a nanocrystalline polymer composite, where the nanocrystals act as a source of protons in the system and the polymer acts as a conducting matrix for the protons. Previous attempts to boost the performance of proton exchange membranes, including the addition of inorganic components, were based on the idea of ​​conserving water in the system by having either a hydrophilic surface or micropores that can promote capillary condensation. On the other hand, the approach described herein is based on the interfacial proton conductivity presented by the porous nanocrystalline metal oxide.

[0069] Herein, we present the aforementioned concepts involving boosting conductivity by introducing a suitable proton conducting matrix. The demonstration takes advantage of the phenomenon of mid-temperature proton conductivity at metal oxide surfaces to boost conductivity to relevant proton conducting performance for device operation, whether in high temperature fuel cells or electrolysis.

[0070] method Nanocrystal synthesis In a typical synthesis of 4 nm cerium oxide nanocrystals, 0.868 g (2 mmol, Sigma 99.999%) cerium nitrate hexahydrate and 5.36 g (20 mmol, 90% Acros Organics) oleylamine were dissolved in 10 ml 1-octadecene (Aldrich 90%). After initial mixing, the solution was stirred at 80° C. under nitrogen for 1 hour, followed by degassing at 120° C. under a vacuum of <100 mTorr for 1 hour. The solution was then heated to 230° C. Once the solution temperature reached 230° C., the solution was further heated to 250° C. and reacted at 250° C. for 2 hours. After 2 hours, the solution was allowed to cool in air to below 80° C., at which point 5 mL of toluene was added to the solution. The mixture was then centrifuged at 1500 rpm for 10 minutes to remove the bulk precipitate. The supernatant was mixed with 60 mL of isopropanol and centrifuged at 7000 rpm for 10 min. After synthesis, the nanocrystals were washed three times with a combination of hexane / isopropanol for dispersion and precipitation, filtered using a 0.2 μm PTFE filter, and stored.

[0071] Ligand exchange For a typical ligand stripping procedure, nanocrystals suspended in hexane (Aldrich >95% n-hexane) were purified by four cycles of suspension and precipitation with hexane and reagent alcohol or acetone. The concentration of the nanocrystals was then diluted to 5 mg / mL, and an equal volume of N,N-dimethylformamide (DMF) (Aldrich ≥99%) was added to form a biphasic mixture. The biphasic mixture was then shaken to ensure proper washing of the nanocrystals prior to ligand stripping. If the biphasic mixture became cloudy upon shaking, the nanocrystals were allowed to settle and washed two more times, and the test was repeated. If the mixture remained clear and the phases separated back into a biphasic mixture, nitrosyl tetrafluoroborate (Aldrich 95%) equivalent to half the weight of the nanocrystals in solution or up to the approximate weight of the nanocrystals in solution was added to the mixture, and the mixture was then sonicated for 30 minutes to facilitate ligand stripping. After phase transfer from hexane to DMF, the hexane phase was removed and replaced with fresh hexane and shaken. After phase separation, the hexane phase was removed and this hexane wash was repeated two more times. The nanocrystals in DMF were then purified using a combination of DMF / toluene for suspension and precipitation up to six times, varying the DMF:toluene ratio from 1:2, 1:3, 1:4 to a final ratio of 1:6. For the final wash, the nanocrystals were resuspended in 500 μL of DMF, followed by the addition of 500 μL of ethanol. The nanocrystal solution was then vigorously mixed with toluene, resuspended in anhydrous DMF and stored.

[0072] Preparation of polymer-nanocrystal solutions To prepare the composite solutions, the ligand-stripped nanocrystals were mixed with separate polymer solutions in a suitable solvent (dimethylformamide, dimethylacetamide, acetonitrile) and mixed for at least 30 min. The bulk densities of the nanocrystals and polymer were used to adjust the volume fractions. Typical solution concentrations were on the order of 20-100 mg / ml nanocrystals and 1-20 mg / ml polymer.

[0073] Thin film deposition Silicon wafers or quartz substrates were cut into 1 cm x 1 cm substrates and sequentially cleaned using sonication in Hellmanex, ethanol, chloroform, acetone, and isopropanol for 15 min, and UV ozone for 15 min. Polymer nanocrystal films were spin-cast using 20 μL of the composite solution at 1000 rpm for 3 min with a 2 s ramp-up for a typical 400 nm film, followed by drying at 4000 rpm for 1 min.

[0074] Platinum contact deposition A 400 nm film of Pt was sputtered onto the upper surface of the nanocrystal film using a shadow mask defining a 1 mm gap in the center using a Cooke RF sputtering system operating at 60 watts and 1.5 mTorr Ar pressure at a deposition rate of 10 nm / min. The chamber pressure was evacuated to <1e-6 Torr before the introduction of Ar to minimize adventitious contamination from oxygen.

[0075] Impedance spectroscopy Impedance spectroscopy was performed in a two-point configuration using a Novocontrol Alpha-A impedance analyzer over a frequency range of 1 MHz to 1-10 Hz with a voltage amplitude of 0.12 V. A custom stage allowing independent temperature and environmental control was used. An oxygen trap (Agilent OT1-4) was flushed with inert gas and CO was added prior to flow into the stage. 2 and H 2 All gas was passed through the O trap. 2 Moisture was introduced into the cell by bubbling the solution through water set at 17°C, which corresponds to approximately 20 mbar O. After an initial equilibration of 30 min at each temperature, the samples were equilibrated for 6 h at 450°C and 2 h at all other temperatures between 450°C and 100°C, with one measurement every 30 min at 1 Hz or 0.1 Hz from 1 MHz. Conductivity values ​​were normalized to the sample film thickness. Oxygen partial pressure was measured using a Cambridge Sensotech Rapidox 2100 Oxygen Analyzer.

[0076] result Figures 3-6 show examples of prototypical materials for the fabrication of nanocrystal-polymer composites used to demonstrate the concepts outlined above. Figure 3 shows a transmission electron microscope image of the cerium oxide nanocrystals used to imbue the composite with medium temperature proton conductivity, and Figure 4 shows its X-ray diffraction pattern. The nanocrystalline material has an average diameter of 4 nm and is indexed to the standard cubic fluorite structure of cerium oxide. Figures 5 and 6 are scanning electron microscope images of cerium oxide-polymer composites fabricated at a 50:50 volume fraction. In Figures 5 and 6, the nanocrystals appear bright against the polymer, which appears darker and gray.

[0077] Figures 7-9 show the prototype performance improvement observed for the nanocomposite versus its individual counterparts. Figures 7 and 8 are the conductivity of nanocrystal-only and polymer-only films, respectively. Figure 9 illustrates the two orders of magnitude improvement in ionic conductivity of the nanocomposite versus its individual counterparts. For this demonstration, a standard ether polymer (polyethylene oxide) known to be a good ionic conductor was used to form the composite. PEO has a limited thermal stability window below 200°C. However, both the nanocrystal-only (Figure 7) and PEO-only (Figure 8) cases showed poor ionic conductivity. For the former, the low ionic conductivity may be due to the lack of a conducting matrix that provides ionic conductivity mobility. For the latter, the low ionic conductivity may be due to the lack of ions to conduct. When the components were combined, a composite was observed that showed significant ionic conductivity, reminiscent of PEO mixed with a standard ionic salt (Figure 9). This enhanced conductivity was moderately temperature dependent and was further improved by the dissociative adsorption of water on the cerium oxide surface due to the generation of additional mobile protons in the presence of a humid "wet" environment.

[0078] [Example 2] Proton exchange membranes are used to transport protons between the negative and positive electrodes during charging and discharging in proton exchange membrane fuel cells (PEMFCs) or some electrochromic devices. There are a variety of materials with proton conductivity ranging from polymeric systems such as Nafion to fully inorganic systems such as solid acids.

[0079] In polymer ion exchange membranes, especially proton exchange membranes at high temperatures, one of the most important challenges is the placement of water, since these membranes depend on water for mobile protons, which are responsible for proton conductivity. Many polymer systems, especially Nafion, dehydrate above the boiling point of water (100 °C) and lose conductivity as a result. For example, the polymer material that serves as the proton exchange membrane in PEMFC is Nafion, which is conductive below 100 °C, but above 100 °C Nafion dehydrates and the material no longer exhibits good conductivity. Fully inorganic systems, such as solid acids, are inherently unstable at the operating conditions due to their sensitivity to humidity. These limitations cumulatively directly result in an upper limit of the operating temperature window for proton exchange membrane fuel cells (PEMFCs) at 90 °C. This is in direct opposition to the current push to operate PEMFCs at higher temperatures, e.g., above 100°C, for electrochemical efficiency and stability gains; for example, fuel cells can operate with faster reaction rates, higher voltage gains, and less susceptibility to coking at higher temperatures. Also, at higher operating temperatures, thermal energy can support activation in catalytic processes in PEMFCs, mass diffusion losses are reduced, and platinum catalysts are less susceptible to carbon monoxide poisoning.

[0080] Porous proton transport composites containing nanoscale metal oxides exhibit medium temperature proton conductivity (100°C-300°C) under humid (wet gas) conditions and may be useful as robust proton transport membranes or electrolytes, especially at temperatures above 100°C. However, one limitation of the surface-mediated protonic conductivity exhibited by porous metal oxides under humid conditions is that despite persistence at high temperatures, absolute conductivity is limited. Notably, the proton conductivity of such nanoscale metal oxides is several orders of magnitude lower than that required for practical proton transport materials (current industry requirements for fuel cell applications >10°C). -3 10 for S / cm -6 (S / cm).

[0081] Described herein are nanostructured inorganic-organic composites that can be used for proton conduction as solid electrolytes at moderate temperatures (e.g., 100°C or higher, 200°C or higher, up to 300°C). The composites can exhibit high ionic conductivity at 100°C to 200°C or higher, which is comparable to state-of-the-art polymeric conducting membranes (improving them at higher temperatures within this range). In addition, the composites show up to five orders of magnitude increase in conductivity compared to inorganic-only systems containing only metal oxides. The composites can widen the operating window for proton exchange membranes with good and usable conductivity well above 100°C to 200°C or higher, allowing the construction of fuel cells that can operate more efficiently with faster reaction rates, higher voltage gains, and less susceptibility to coking.

[0082] Disclosed herein are compositions of composite organic-inorganic proton conducting materials composed of nano-sized, high surface area crystalline metal oxides and organic conductive matrices, as well as methods for making said compositions. The composite materials utilize nanocrystalline metal oxides that exhibit preferential adsorption of water on the surface and water dissociation at defect sites to both retain water and generate mobile protons. The composite materials also use the introduction of organic matrices, either by ex situ or in situ means, to provide conductive pathways for protons, thereby dramatically increasing the absolute ionic conductivity of the composite materials.

[0083] The composite materials described herein build medium temperature proton conduction on the open surface of the metal oxide by enhancing the conductivity using a polymer matrix that forms an interfacial region with the porous nanostructured metal oxide and facilitates conduction, increasing the conductivity to an acceptable level for practical applications. To demonstrate this concept, an in situ polymerization method was used to form the exemplary composite materials, and a stable proton conductivity enhancement of nearly five orders of magnitude was observed. The in situ method is scalable and directly applicable, especially in the case of thin-film electrolytes. Thus, the composite materials and the methods for making them can be cost-effective and durable. The composite materials described herein can be used in fuel cells, proton exchange membranes, ion exchange membranes, and reversible electrodialysis.

[0084] Proton transport in the composite materials described herein can be enhanced by coating the metal oxide surface with a proton transporting polymer matrix. Many such polymers are known from previous developments in polymer-only electrolytes and hybrid polymer-inorganic electrolytes, one such class of polymers being polyethers such as polytetrahydrofuran. In a composite demonstration, a thin layer of polytetrahydrofuran is coated on the porous CeO 2 The in situ deposition of nanocrystals into the film significantly increased the proton conductivity (up to five orders of magnitude) by providing a matrix for proton conductivity, and the conductivity of the composite persisted into the higher moderate temperature regimes where previous polymer-based proton conductors have typically slumped.

[0085] Nanocomposites vs. CeO when the polymer used to form the composite is polybenzimidazole 2 Results showing the performance improvement observed for the nanocrystals alone are shown in Figure 10 (composite was tested twice). 2 A two order of magnitude improvement in ionic conductivity at 450° C. of the nanocomposite versus the nanocrystals alone is demonstrated.

[0086] Herein, we have combined polymeric materials and inorganic metal oxides to create synergistic composite materials in which the polymer matrix provides an efficient conductivity pathway while the metal oxide provides proton retention at high temperatures. These composite materials are applicable to any type of interface-driven proton transport device, such as ion exchange membranes, particularly proton exchange membranes for proton exchange membrane fuel cells or micro-fuel cells.

[0087] The compositions, devices and methods of the appended claims are not limited in scope by the specific devices and methods described herein, but are intended as examples of some embodiments of the claims, and any devices and methods that are functionally equivalent are within the scope of the present disclosure. In addition to those shown and described herein, various variations of the compositions, devices and methods are intended to be within the scope of the appended claims. Furthermore, only certain representative compositions, devices and methods of the compositions, devices and methods of the present invention are specifically described, but combinations of various features of other compositions, devices and methods of these compositions, devices and methods are intended to be within the scope of the appended claims, even if not specifically described. Thus, although a combination of steps, elements, components or structures may be explicitly described herein, all other combinations of steps, elements, components and structures are included, even if not explicitly described. Based on the above description, examples of the present invention include the following. [1] A composite film comprising a plurality of nanostructured metal oxide crystals dispersed within a proton conducting polymer phase, the plurality of nanostructured metal oxide crystals having an average particle size of 1 nm to 20 nm, and comprising 20% ​​to 90% by volume of the composite film. [2] The composite film of [1] above, wherein the plurality of nanostructured metal oxide crystals comprises a reducible metal oxide. [3] The composite film of [1] or [2] above, wherein the plurality of nanostructured metal oxide crystals comprises niobium oxide, titanium oxide, tungsten oxide, zirconium oxide, hafnium oxide, magnesium oxide, vanadium oxide, iron oxide, chromium oxide, manganese oxide, nickel oxide, cerium oxide, gadolinium oxide, samarium oxide, or a combination thereof. [4] The composite film according to any one of [1] to [3] above, wherein the plurality of nanostructured metal oxide crystals comprises niobium oxide, titanium oxide, tungsten oxide, hafnium oxide, vanadium oxide, iron oxide, chromium oxide, manganese oxide, nickel oxide, cerium oxide, gadolinium oxide, samarium oxide, or a combination thereof. [5] The composite film according to any one of the above [1] to [4], wherein the plurality of nanostructured metal oxide crystals comprises cerium oxide. [6] The composite film described in any one of [1] to [5] above, wherein the plurality of nanostructured metal oxide crystals comprises cerium oxide doped with one or more dopants. [7] The composite film of any one of [1] to [6] above, wherein the plurality of nanostructured metal oxide crystals comprises gadolinium-doped cerium oxide, samarium-doped cerium oxide, or a combination thereof. [8] A composite film described in any one of [1] to [7] above, wherein each of the plurality of nanostructured metal oxide crystals has at least one dimension having a size of 1 nm to 5 nm. [9] The composite film according to any one of the above [1] to [8], wherein the plurality of nanostructured metal oxide crystals have an average particle shape that is substantially isotropic.

[10] The composite film described in any one of [1] to [9] above, wherein the plurality of nanostructured metal oxide crystals have an average particle size of 1 nm to 10 nm.

[11] The composite film described in any one of [1] to

[10] above, wherein the plurality of nanostructured metal oxide crystals are substantially free of ligands and / or capping materials.

[12] The composite film according to any one of the above [1] to

[11] , wherein the proton-conducting polymer phase comprises a polyether, a polysulfonate, a polysulfone, a poly(imidazole), a triazole, a benzimidazole, a polyester, a polycarbonate, a polymer derived from a pyridine monomer, a derivative thereof, or a combination thereof.

[13] The composite film according to any one of the above [1] to

[12] , wherein the proton-conducting polymer phase contains a polyether or a derivative thereof.

[14] The composite film according to any one of [1] to

[13] above, wherein the proton-conducting polymer phase comprises polyethylene oxide, polyetherpyridine, polyetheretherketone (PEEK), polytetrahydrofuran, polyvinylbutyral, polybenzimidazole, a derivative thereof, or a combination thereof.

[15] The composite film according to any one of the above [1] to

[14] , wherein the proton-conducting polymer comprises polyethylene oxide, polytetrahydrofuran, a derivative thereof, or a combination thereof.

[16] The composite film described in any one of [1] to

[15] above, wherein the plurality of nanostructured metal oxide crystals are contained in an amount of 30 to 90 volume %, 20 to 70 volume %, or 20 to 50 volume % of the composite film.

[17] The composite film according to any one of the above [1] to

[16] , having an average thickness of 100 nm to 500 μm, 1 μm to 500 μm, or 10 μm to 100 μm.

[18] At temperatures above 100°C, 200°C or 300°C, -8 S / cm or more, 10 -6 S / cm or more, 10 -4 The composite film according to any one of the above [1] to

[17] , having a proton conductivity of 0.1 S / cm or more, 0.01 S / cm or more, or 0.1 S / cm or more.

[19] The composite film according to any one of the above [1] to

[18] , which forms a self-supporting film.

[20] The composite film according to any one of the above [1] to

[18] , which is supported by a substrate.

[21] A method for producing the composite film according to any one of the above [1] to

[20] , dispersing the plurality of nanostructured metal oxide crystals and a polymer comprising the proton conducting polymer phase in a solvent, thereby forming a dispersion; depositing the dispersion onto a substrate; and thereby forming said composite film. A method comprising:

[22] The method of

[21] above, wherein the solvent comprises tetrahydrofuran (THF), dimethylformamide (DMF), N-methylformamide, formamide, acetonitrile, dimethylacetamide, propylene carbonate, ethylene carbonate, n-methylpyrrolidone, dimethylsulfoxide, or a combination thereof.

[23] The method according to

[21] or

[22] above, wherein the solvent comprises dimethylformamide, dimethylacetamide, acetonitrile, or a combination thereof.

[24] The method according to any one of

[21] to

[23] above, wherein the step of depositing the dispersion comprises printing, spin coating, drop casting, zone casting, dip coating, blade coating, spraying, vacuum filtration, slot die coating, curtain coating, or a combination thereof.

[25] The method according to any one of the above

[21] to

[24] , wherein the step of depositing the dispersion comprises spin coating.

[26] The method according to any one of the above

[21] to

[25] , further comprising the step of removing the composite film from the substrate.

[27] The method according to any one of

[21] to

[26] above, further comprising the step of producing the plurality of nanostructured metal oxide crystals.

[28] The method according to any one of

[21] to

[27] above, further comprising the step of removing ligands and / or capping agents from the plurality of nanostructured metal oxide crystals such that the plurality of nanostructured metal oxide crystals are substantially free of ligands and / or capping materials.

[29] A device comprising the composite film according to any one of the above [1] to

[20] , the device constituting a fuel cell, an electrolytic cell, a proton exchange electrolyzer or a battery.

[30] The device according to

[29] above, constituting a proton exchange membrane fuel cell (PEMFC).

[31] The device according to

[29] or

[30] above, operated at a temperature of 25°C or more, 50°C or more, 100°C or more, 200°C or more or 300°C or more.

[32] A method for using the composite film described in any one of [1] to

[20] above, comprising a step of using the composite film as a proton exchange membrane, an ion exchange membrane, a hydrogen separation membrane, a solid electrolyte, or a combination thereof.

[33] A method for using the composite film according to any one of the above [1] to

[20] , comprising the step of using the composite film in a fuel cell.

[34] The method according to

[32] or

[33] above, comprising using the composite film as a proton exchange membrane in a proton exchange membrane fuel cell (PEMFC).

[35] The method according to any one of

[32] to

[34] above, wherein the method is carried out at a temperature of 25°C or higher, 50°C or higher, 100°C or higher, 200°C or higher, or 300°C or higher.

[36] A method for using the composite film according to any one of [1] to

[20] above, comprising using the composite film in electrolysis, in reversible electrodialysis, in a chlor-alkali system, or in a combination thereof.

Claims

1. 1. A composite film comprising a plurality of nanostructured metal oxide crystals dispersed within a proton conducting polymer phase, the plurality of nanostructured metal oxide crystals having an average particle size of 1 nm to 20 nm and a monodisperse particle size distribution with 80% within 25% of the median particle size, the plurality of nanostructured metal oxide crystals comprising 20% ​​to 90% by volume of the composite film, with the proviso that the plurality of nanostructured metal oxide crystals are not metal oxide hydrates.

2. The composite film of claim 1 , wherein the plurality of nanostructured metal oxide crystals comprises a reducible metal oxide.

3. 3. The composite film of claim 1 or 2, wherein the plurality of nanostructured metal oxide crystallites comprises niobium oxide, titanium oxide, tungsten oxide, zirconium oxide, hafnium oxide, magnesium oxide, vanadium oxide, iron oxide, chromium oxide, manganese oxide, nickel oxide, cerium oxide, gadolinium oxide, samarium oxide, or combinations thereof.

4. 4. The composite film of any one of claims 1 to 3, wherein the plurality of nanostructured metal oxide crystallites comprises niobium oxide, titanium oxide, tungsten oxide, hafnium oxide, vanadium oxide, iron oxide, chromium oxide, manganese oxide, nickel oxide, cerium oxide, gadolinium oxide, samarium oxide, or combinations thereof.

5. The composite film of any one of claims 1 to 4, wherein the plurality of nanostructured metal oxide crystals comprises cerium oxide.

6. The composite film of any one of claims 1 to 5, wherein the plurality of nanostructured metal oxide crystallites comprises cerium oxide doped with one or more dopants.

7. 7. The composite film of any one of claims 1 to 6, wherein the plurality of nanostructured metal oxide crystallites comprises gadolinium doped cerium oxide, samarium doped cerium oxide, or a combination thereof.

8. 8. The composite film of any one of claims 1 to 7, wherein each of the plurality of nanostructured metal oxide crystallites has at least one dimension that is between 1 nm and 5 nm in size.

9. The composite film of any one of claims 1 to 8, wherein the plurality of nanostructured metal oxide crystallites have an average grain shape that is substantially isotropic.

10. The composite film of any one of claims 1 to 9, wherein the plurality of nanostructured metal oxide crystallites has an average grain size of 1 nm to 10 nm.

11. The composite film of any one of claims 1 to 10, wherein the plurality of nanostructured metal oxide crystals is substantially free of ligands and / or capping materials.

12. 12. The composite film of any one of claims 1 to 11, wherein the proton conducting polymer phase comprises a polyether, a polysulfonate, a polysulfone, a poly(imidazole), a triazole, a benzimidazole, a polyester, a polycarbonate, a polymer derived from a pyridine monomer, a derivative thereof, or a combination thereof.

13. The composite film of any one of claims 1 to 12, wherein the proton conducting polymer phase comprises a polyether or a derivative thereof.

14. 14. The composite film of any one of claims 1 to 13, wherein the proton conducting polymer phase comprises polyethylene oxide, polyetherpyridine, polyetheretherketone (PEEK), polytetrahydrofuran, polyvinylbutyral, polybenzimidazole, derivatives thereof, or combinations thereof.

15. The composite film of any one of claims 1 to 14, wherein the proton conducting polymer comprises polyethylene oxide, polytetrahydrofuran, derivatives thereof, or combinations thereof.

16. 16. The composite film of any one of claims 1 to 15, comprising 30-90%, 20-70% or 20-50% by volume of the nanostructured metal oxide crystals relative to the composite film.

17. 17. The composite film of any one of claims 1 to 16, having an average thickness of from 100 nm to 500 μm, from 1 μm to 500 μm, or from 10 μm to 100 μm.

18. At temperatures of 100°C or higher, 200°C or higher, or 300°C or higher, -8 S / cm or more, 10 -6 S / cm or more, 10 -4 18. The composite film of claim 1, having a proton conductivity of 0.1 S / cm or more, 0.01 S / cm or more, or 0.1 S / cm or more.

19. The composite film of any one of claims 1 to 18, which forms a self-supporting film.

20. The composite film of any one of claims 1 to 18, which is supported by a substrate.

21. A method for producing a composite film according to any one of claims 1 to 20, comprising the steps of: dispersing the plurality of nanostructured metal oxide crystals and a polymer comprising the proton conducting polymer phase in a solvent, thereby forming a dispersion; depositing the dispersion onto a substrate; and thereby forming said composite film. A method comprising:

22. 22. The method of claim 21, wherein the solvent comprises tetrahydrofuran (THF), dimethylformamide (DMF), N-methylformamide, formamide, acetonitrile, dimethylacetamide, propylene carbonate, ethylene carbonate, n-methylpyrrolidone, dimethylsulfoxide, or a combination thereof.

23. 23. The method of claim 21 or 22, wherein the solvent comprises dimethylformamide, dimethylacetamide, acetonitrile, or a combination thereof.

24. 24. The method of any one of claims 21 to 23, wherein depositing the dispersion comprises printing, spin coating, drop casting, zone casting, dip coating, blade coating, spraying, vacuum filtration, slot-die coating, curtain coating, or a combination thereof.

25. The method of any one of claims 21 to 24, wherein the step of depositing the dispersion comprises spin-coating.

26. The method of any one of claims 21 to 25, further comprising removing the composite film from the substrate.

27. The method of any one of claims 21 to 26, further comprising producing the plurality of nanostructured metal oxide crystals.

28. 28. The method of any one of claims 21 to 27, further comprising removing ligands and / or capping agents from the plurality of nanostructured metal oxide crystals such that the plurality of nanostructured metal oxide crystals is substantially free of ligands and / or capping materials.

29. A device comprising a composite film according to any one of claims 1 to 20, comprising a fuel cell, an electrolyser, a proton exchange electrolyser or a battery.

30. 30. The device of claim 29 comprising a proton exchange membrane fuel cell (PEMFC).

31. 31. The device of claim 29 or 30, operated at a temperature of 25°C or more, 50°C or more, 100°C or more, 200°C or more, or 300°C or more.

32. 21. A method of use of the composite film according to any one of claims 1 to 20, comprising using said composite film as a proton exchange membrane, as an ion exchange membrane, as a hydrogen separation membrane, as a solid electrolyte or a combination thereof.

33. A method of use of a composite film according to any one of claims 1 to 20, comprising using said composite film in a fuel cell.

34. 34. The method of claim 32 or 33, comprising using the composite film as a proton exchange membrane in a proton exchange membrane fuel cell (PEMFC).

35. 35. The method of any one of claims 32 to 34, carried out at a temperature of at least 25°C, at least 50°C, at least 100°C, at least 200°C or at least 300°C.

36. 21. A method of use of the composite film according to any one of claims 1 to 20, comprising using the composite film in electrolysis, in reversible electrodialysis, in a chlor-alkali system, or a combination thereof.

Citation Information

Patent Citations

  • Electrolyte composite body

    JP1993314995A

  • Fuel cell of MEMS (micro electronic mechanical system) base and method

    JP2004165148A

  • Complex electrolyte membrane for fuel cell, manufacturing method thereof, membrane electrode assembly, and fuel cell

    JP2008300135A

  • Proton conductive composite electrolyte membrane, and membrane electrode assembly and fuel cell using the same

    JP2010138325A

  • Inorganic particle aggregate and method of manufacturing gas diffusion electrode

    JP2011086572A